THE EFFECT OF HEALTHY LIFESTYLE EDUCATION ON THE LEVEL OF KNOWLEDGE OF HYPERTENSION CONTROL IN THE ELDERLY IN GBI BUKIT PENGHARAPAN KEDIRI - Maria Nubatonis; Dinar Yuni A. A. C (Suluh Adiluhung Publisher (SAPub), 2026)
Hypertension is a silent killer with long-term and dangerous impacts if left untreated. Prevention can be achieved through a healthy lifestyle. This study aimed to determine the effect of healthy lifestyle education on knowledge of hypertension control in the elderly. This was a quasi-experimental study with a one-group pretest-posttest design, involving 45 elderly students aged 60-79 years selected using purposive sampling. Data were collected through questionnaires and analyzed using frequency distribution and the Wilcoxon test. After receiving education, all respondents (100%) demonstrated good knowledge of hypertension control. The statistical test showed a p-value of 0.000 (<0.05), indicating a significant change in respondents' attitudes. Providing education on healthy lifestyles has been shown to have a positive effect on knowledge of hypertension control in the elderly at GBI Bukit Pengharapan in 2026. The elderly are encouraged to adopt a healthy lifestyle by exercising regularly, maintaining a balanced diet, limiting salt, and managing stress to prevent hypertension early.